Legal Protection for Patients in Telemedic Services in Indonesia - Rohmatul Hajiriah Nurhayati; I Wayan Parsa; Sagung Putri M.E Purwani (Dinasti Research, 2025)
The development of information and communication technology had a significant impact on various sectors, including the health sector. One of the main innovations is telemedicine, namely a long-distance health service that utilizes technology for medical consultations between patients and medical personnel. This service is increasingly important, especially in Indonesia, which has a large and diverse geographical area. The COVID-19 pandemic has also accelerated the adoption of telemedicine. However, various legal challenges arise related to protecting patient rights, such as data privacy, obligations of medical personnel, and regulatory oversight. This research aims to analyze legal protection for patients in telemedicine services in Indonesia, with a focus on the importance of clear and comprehensive regulations. The method used is normative legal research, which analyzes legal regulations, laws and guidelines governing telemedicine services, as well as relevant legal principles. The research results show that the legal aspect of patient protection includes important aspects such as confidentiality of medical data, quality of service, informed consent, professional responsibility of medical personnel, and the right to access medical records. Doctors who carry out telemedicine must be registered and have a valid practice license, as well as maintain confidentiality and provide services according to standards. Although telemedicine provides many benefits, strict oversight and regulatory compliance are essential to ensure patient safety and protection.